Analisis risiko keselamatan kerja dan strategi mitigasi berbasis HIRA pada operasional kapal cantrang di PPP Tegalsari - Singgih; Adi Susanto; Nurhasanah (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study intends to evaluate potential hazards, assess risk levels, and provide safety mitigation techniques for the Cantrang crew at the Tegalsari Coastal Fisheries Port (PPP), Tegal City. The employed research methodology is a mixed-methods strategy incorporating Hazard Identification and Risk Assessment (HIRA) alongside Formal Safety Assessment (FSA) analytical methodologies. The study's findings indicate that most work activities on Cantrang vessels fall under the Medium to High-risk category. The phases of towing and hauling operations were recognized as the most critical, with the highest risk scores of 16 and 15, respectively. This elevated risk is caused by mechanical dangers associated with fishing equipment, non-ergonomic work postures, and chronic exhaustion resulting from excessive work schedules, averaging 16.5 hours of labor per day with merely 6 hours of respite. Moreover, systemic deficiencies were identified due to the lack of documented safety Standard Operating Procedures (SOPs), and 68% of crew members lacked valid safety certifications. According to the analysis of HIRA and FSA, the proposed mitigation strategies encompass technical interventions such as the installation of guards on winches, administrative controls via the implementation of fatigue management SOPs in accordance with ILO C188 standards, and the enhancement of safety culture through on-board safety training. The execution of this approach is anticipated to rectify latent weaknesses and establish a sustainable occupational safety system within the conventional catch fisheries sector. Keywords: Work Safety, Cantrang Ships, HIRA, FSA, Risk Mitigation ABSTRAK Penelitian ini bertujuan untuk menganalisis potensi bahaya, tingkat risiko, dan merumuskan strategi mitigasi keselamatan kerja pada awak kapal cantrang di Pelabuhan Perikanan Pantai (PPP) Tegalsari, Kota Tegal. Metode penelitian yang digunakan adalah pendekatan campuran (mixed-methods) dengan teknik analisis Hazard Identification and Risk Assessment (HIRA) dan Formal Safety Assessment (FSA). Hasil penelitian menunjukkan bahwa mayoritas aktivitas kerja pada kapal cantrang berada dalam kategori risiko Sedang hingga Tinggi. Tahapan operasi towing (penarikan jaring) dan hauling (pengangkatan hasil tangkapan) diidentifikasi sebagai fase paling kritis dengan skor risiko tertinggi masing-masing sebesar 16 dan 15. Tingginya risiko ini dipicu oleh bahaya mekanis peralatan tangkap, postur kerja non-ergonomis, serta kelelahan kronis akibat pola kerja ekstrem dengan rata-rata durasi kerja 16,5 jam per hari dan waktu istirahat hanya 6 jam per hari. Selain itu, ditemukan kegagalan sistemik berupa ketiadaan SOP keselamatan tertulis dan 68% awak kapal tidak memiliki sertifikasi keselamatan formal. Berdasarkan analisis HIRA dan FSA, strategi mitigasi yang direkomendasikan meliputi intervensi teknis berupa pemasangan guarding pada winch, pengendalian administratif melalui penegakan SOP manajemen kelelahan sesuai standar ILO C188, serta penguatan budaya keselamatan melalui on-board safety training. Implementasi strategi ini diharapkan dapat menutup latent failures dan menciptakan sistem keselamatan kerja yang berkelanjutan di sektor perikanan tangkap tradisional. Kata-kata kunci: Keselamatan Kerja, Kapal Cantrang, HIRA, FSA, Mitigasi Risiko